Solitary fibrous tumors of the oral and maxillofacial region: a case series from a single-center - Chaowei Wang; Bo Wang; Jianfeng He (BMC, 2024)
Abstract Background Solitary fibrous tumor (SFT) is a rare mesenchymal lesion that has a wide anatomic distribution. However, this lesion rarely occurs in the oral or maxillofacial region. Methods A retrospective review was performed to evaluate the clinical symptoms, radiological images, pathology and immunohistochemistry results of 9 patients with SFTs treated between January 2015 to April 2024 in our institute. Surgical tumor resection was administered to all patients. Follow-up for these patients spanned until the conclusion of April 2024. Results The series contained 3 males and 6 females, with the mean age 50.6 years (range: 25 to 73 years). The tumors were distributed at six different sites, including the tongue, submandibular region, cheek, sublingual gland, mandible, and hard palate. Clinically, the mass grew gradually and usually without obvious clinical symptoms. On imaging examination, the boundaries of all the tumors were clear, except for one patient with a mandibular tumor. Surgical excision was performed in all patients. Histological characteristics and positive immunostaining for STAT6, CD99, CD34 and Bcl-2 were the most important criteria for a final diagnosis. All tumors were positive for CD34 and Bcl-2. Only one tumor was negative for STAT6. While CD99 was negative in one case and weakly positive in two cases. All patients had no local recurrence during the follow-up period ranging from 1 to 100 months (mean 41.4 months). Conclusions Benign SFTs occurring in the oral and maxillofacial region are rare, and surgery is the primary treatment for this tumor. It usually presents as a distinctly bordered heterogeneous mass on imaging. The tumors can compress surrounding bone tissue leading to bone resorption, and in rare cases, it may exhibit invasive resorption. SFTs should be included in the differential diagnosis of lesions in the oral and maxillofacial region.